Well-defined protein immobilization on photo-responsive phosphorylcholine polymer surfaces. Issue 17 (22nd November 2017) - Tanaka, Masako; Kawai, Shugo; Iwasaki, Yasuhiko
Abstract: In this study, we propose a new polymer substrate that is able to covalently couple intended proteins and reduce nonspecific protein fouling. Poly[2-methacryloyloxyethyl phosphorylcholine (MPC)-ran- N -methacryloyl-(L)-tyrosinemethylester (MAT)] [P(MPC/MAT)] was synthesized by free-radical polymerization. The photooxidation of the MAT unit in the copolymer was observed under ultraviolet (UV) light at 254 nm. P(MPC/MAT) was spin-coated on silicon (Si) and gold substrates. Without UV irradiation of the polymer-coated surface, P(MPC/MAT) physisorbed on the substrates, and the thickness of the polymer layer was less than 10 nm, regardless of the polymer concentration in the coating solution. In contrast, when the polymer-coated surface was irradiated with UV light, the thickness of the polymer layer could be controlled by changing the polymer concentration of the coating solution. Competitive protein adsorption on P(MPC/MAT) was studied. Bovine serum albumin was first contacted with the surface and later challenged with bovine fibrinogen. On bare gold and Si substrates, a large amount of albumin was adsorbed, and the competitive adsorption of albumin and fibronectin was observed. In contrast, the non-UV-irradiated P(MPC/MAT) surface effectively reduced protein adsorption. Interestingly, on the UV-irradiated P(MPC/MAT) surface, the primary protein preferably bonded, and significantly less secondary protein was adsorbed compared to primary protein. Cell adhesion was also tested on the substrate to clarify the effects of proteins existing on the substrates. On the bare Si surface, many adherent cells were observed, regardless of the protein pretreatment. On the non-UV-irradiated P(MPC/MAT) surface, cell adhesion was effectively reduced along with protein adsorption. Cell adhesion on the UV-irradiated P(MPC/MAT) surface depended strongly on the type of protein that was initially in contact with the surface. We concluded that the desired proteins could be immobilized on the photo-activated P(MPC/MAT) surface while preserving their function. Moreover, competitive protein exchange and multilayer adsorption hardly occurred on the surface.